A Review on Smart Energy Grid Technology: Features and Specifications - Mahmoud M.A.; Tang A.Y.C.; Maseleno A.; Lim F.-C.; Kasim H.; Yong C.; Mostafa S.A. (Asian Research Publishing Network, 2023)
Although, it is widely recognized that smart grid technology is a necessity to reduce the impact of global warming while encouraging efficiency, reliability and effective governance in the supply of electrical energy, the understanding of smart grid technology among researchers is limited. To provide a clear insight to this problem and support researchers, we need a background understanding of various aspects related to smart grid. Current electricity transmission and distribution networks can be categorized as conventional electricity networks because they have not been able to provide excellent service and present real-time data. This network has not been able to provide reliability, safety and efficiency in supplying electrical energy even not yet have the flexibility to be integrated with the generation of renewable energy or microgrid. In this study, a comprehensive review is conducted to map the literature studies to a coherent taxonomy. These include the features and specifications of smart grid. The fundamentals of smart grid presented in this study can benefit readers who wish to embark in smart grid research and applications development. Medwell Journals, 2020